Prospects for Urban Morphology in Resilience Assessment. - Stangl, Paul (Springer, 2018)
Recent attempts to develop resiliency indices for metropolitan areas have relied on coarse aggregate data that has little value in assessing the impacts of hazards on urban life. An examination of literature on three hazards (heat waves, flooding, and fires) reveals that it is essential to consider impacts, and how to mitigate and remediate them at multiple scales. The field of urban morphology offers a ready-made framework for the development of new resiliency assessment criteria at multiple-scales. While a few initial steps have been taken in this direction, an immense untapped potential remains.
Keywords: Stadtentwicklung; Ökologischer Stadtumbau; Morphologie; Resilienz; Naturgefahr; Hitze; Überschwemmung; Sturm; Bewertungsverfahren